Literary Criticism In The Post-Truth Era - Donny Syofyan (Andalas International Journal of Socio-Humanities, 2019)
Post truth relates to circumstances whereby objective facts are less influential in shaping the opinion of the public, rather appealing to personal belief and emotion. Post truth era is bordering a blurry line between lies and truths, dishonesty and honesty, nonfiction and fiction. The entire phenomenon of post truth is about an individual’s opinion being worth more than the facts. As such, the present paper seeks to understand new insights or perspectives in literary criticism in the post truth era. The criticism of the literature was always based on broad schools of thoughts/theories, which were employed for many centuries. Some of the traditional approaches the paper highlights include: formalistic criticism, biographical criticism, historical criticism, gender criticism, psychological criticism, sociological criticism, mythological criticism, reader-response criticism, and deconstructionist criticism. Equally, the paper extensively analyzes some of the new perspectives or insights to literary criticism in the post truth era: reflective approach, didactic approach, partisan approach, and religious approach. In reflective approach to literature criticism in the post truth era, the meaning in the literature is reflected by the outside of its own being. On the other hand, in didactic approach to literature criticism, truth and meaning is taught in the literature. Moreover, in partisan approach to literature criticism, there is the truthful meaning that is already known and can be found in the literature. Lastly, in the religious approach to literature criticism in post truth era, the meaning and truth is the literature itself, while the outside world has nothing to do with it.